2021
DOI: 10.1002/zaac.202100022
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of a copper complex based on the tripodal ligand (2‐aminoethyl)bis(2‐pyridylmethyl)amine (uns‐penp)

Abstract: A new derivative of the ligand (2‐aminoethyl)bis(2‐pyridylmethyl)amine (uns‐penp), capable for covalent immobilization on silica, was synthesized. Silica powder for column chromatography and mesoporous monoliths served as surface material. Functionalized silica was sufficiently characterized with reflectance UV/Vis and FTIR techniques. Copper(I) was successfully complexed with the immobilized ligand and exhibits reversible reactivity towards dioxygen at low temperatures. Suspending the oxygen species with tolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
2
4
0
Order By: Relevance
“…On bubbling the yellow/brown solution with air, the initial green color reappeared and the reformation of the peak at λ = 443 nm was observed (Figure S4d,f). These cycles could be repeated several times before the brown color dominates the solution, and no further reformation of the complex is possible, in line with previous reports. , We also performed additional experiments whereby different volumes of air were added to a deoxygenated solution of CuBr/DMSO/Me 6 TREN and observed a more intense superoxido peak by increasing the air content (Figure S5). Notably, the role of DMSO proved to be essential for the stabilization of the superoxido complex as no other solvent studied yielded the characteristic UV profile.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…On bubbling the yellow/brown solution with air, the initial green color reappeared and the reformation of the peak at λ = 443 nm was observed (Figure S4d,f). These cycles could be repeated several times before the brown color dominates the solution, and no further reformation of the complex is possible, in line with previous reports. , We also performed additional experiments whereby different volumes of air were added to a deoxygenated solution of CuBr/DMSO/Me 6 TREN and observed a more intense superoxido peak by increasing the air content (Figure S5). Notably, the role of DMSO proved to be essential for the stabilization of the superoxido complex as no other solvent studied yielded the characteristic UV profile.…”
Section: Resultssupporting
confidence: 81%
“…Instead, in the second case where all the components (i.e., DMSO/ Me 6 TREN /CuBr) were premixed under an ambient atmosphere prior to deoxygenation (Figure b inset), a very intense green color could be observed suggesting the oxidation of Cu I to Cu II (Figure S4b). This intense green color has been previously attributed to the formation of copper superoxido complexes. It is important to note that this is a much more intense green color when compared to mixing CuBr 2 / Me 6 TREN/DMSO under ambient temperature, which results in a pale green solution (Figure S4c). The aforementioned solutions were subsequently measured by ultraviolet visible (UV–vis) spectroscopy.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…With this peroxido species, the oxidation of toluene could be achieved [13] . More recently, we described the immobilization of a copper(I) complex with derivatives of uns‐penp on silica for the oxidation of toluene [20] . The results of this work could become important for future applications of oxygenation reactions in a flow reactor.…”
Section: Introductionmentioning
confidence: 97%
“…Previously, we demonstrated that it is possible to oxygenate toluene to benzaldehyde using solid binuclear end-on copper peroxido complexes [LCuÀ O 2 À CuL](BPh 4 ) 2 (with L = , for exam-ple Me 6 tren, Scheme 1) [7] or by applying the same compounds immobilized on silica. [8] Furthermore, Karlin and co-workers reported that the corresponding peroxido copper complexes with L = tris(2-methylpyridyl)amine (tmpa) -or derivatives of this ligand -are capable of oxidizing toluene in solution. [9] With these complexes, it was possible to oxidize benzaldehyde at low temperatures with conversions up to 40 %, according to Scheme 1.…”
Section: Introductionmentioning
confidence: 99%